1986
DOI: 10.1007/bf01056570
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of water contaminative phenols through hairless mouse skin

Abstract: As a means of determining the risk of absorption of water contaminative phenolic compounds through the skin, the permeation of a number of phenols, all on the U.S. Environmental Protection Agency's list of priority pollutants, through hairless mouse skin has been studied, using in vitro diffusion cell methods. Experimentally determined permeability coefficients through intact skin and stratum corneum denuded skin and permeability coefficients derived therefrom for the viable tissue layer and the stratum corneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…Most results were well within an order of magnitude of the values for human skin [33]. The results obtained with four phenolic pollutants in the hairless mouse (SKH-hr -1 strain) were in accord with similar data obtained by other researchers with human epidermis [34]. Another study compared skin penetration of a series of phenols in hairless mouse (HRS-hr/hr) with that of human.…”
Section: Ooooooooooooooooosupporting
confidence: 76%
“…Most results were well within an order of magnitude of the values for human skin [33]. The results obtained with four phenolic pollutants in the hairless mouse (SKH-hr -1 strain) were in accord with similar data obtained by other researchers with human epidermis [34]. Another study compared skin penetration of a series of phenols in hairless mouse (HRS-hr/hr) with that of human.…”
Section: Ooooooooooooooooosupporting
confidence: 76%
“…In addition, as the pKa values of the phenols are more than two pH units above the pH of the solutions used, each of the compounds studied was essentially all in the unionised form (>99%). Huq et al (15) reported that the k p of phenolic compounds with a pKa of 7.15 or less varied with the pH of the donor aqueous solution, due to partial ionisation; but our choice of phenolic compounds and solution pH circumvents this problem. Furthermore, the polar surface area (PSA) from SciFinder Scholar 2006, as well as the solvatochromic parameters, solute hydrogen-bond acidity/ basicity (α/β), and dipolarity/polarisability of solute (π) (51)(52)(53), are included to illustrate the H-bonding abilities of the compounds.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Lien and Tong (4) used skin permeability and vasoconstriction data for different solutes to show that the lipophilicity, size and S aq were important. In these studies, the main barrier for skin transport was attributed to the stratum corneum squamae (5,12), with recognition that the underlying viable epidermis and, in vitro, the aqueous diffusion layer (5,6,(13)(14)(15), and dermis (5,16) may also contribute to the skin resistance. In the late 1970s, histochemical (17) and theoretical considerations (7,18) led to recognition that the intercellular lipid in the stratum corneum was probably the most important pathway for solute transport through stratum corneum.…”
Section: Introductionmentioning
confidence: 98%
“…Die Weltgesundheitsorganisation (WHO) [39] Di-und Trichlorphenolen bei der Maus und der Ratte berichten Huq et al [40]. Zur Hautresorption von 2,4,6-Trichlorphenol liegen Erkenntnisse vor: Bei Probanden, die neue Schuhe unmittelbar auf der Haut trugen, konnten bereits einen Tag nach dem Tragen deutlich erhöhte Chlorphenolkonzentrationen im Urin festgestellt werden [14].…”
Section: Aufnahme Metabolismus Und Toxikologieunclassified